2020
DOI: 10.1002/ceat.201900507
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Temperature on Coccolith‐Containing Systems fromEmiliania huxleyiCultivations

Abstract: Thermogravimetric analysis of a coccolith-containing biogenic broth showed a three-step degradation process. According to this system behavior, the biogenic broth was heated to specific temperatures and characterized in terms of its morphology, surface chemistry, and crystallinity. The elemental and organic composition of the treated samples was also evaluated and compared to the reference material. The presented results were acquired in an effort to exploit pretreatment scenarios for such a biogenic system th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
2
5
0
Order By: Relevance
“…The temperature increase induces the entropy of the molecules, reducing their binding ability, which supports the dissolution of the oily and proteinaceous binders from the inorganic components. The temperature with which we are working had no visible impact on the nannofossils, partially corroborating the work of Chairopoulou [106] even though the study of Coto [107] showed an increasing solubility under certain conditions already from 20 °C on the contrary. This procedure alone does not work, but helps the solvent mix with the organic particles, breaks the bonds of the molecules, and reduces the time of disaggregation.…”
Section: Interaction Temperature-chalksupporting
confidence: 86%
“…The temperature increase induces the entropy of the molecules, reducing their binding ability, which supports the dissolution of the oily and proteinaceous binders from the inorganic components. The temperature with which we are working had no visible impact on the nannofossils, partially corroborating the work of Chairopoulou [106] even though the study of Coto [107] showed an increasing solubility under certain conditions already from 20 °C on the contrary. This procedure alone does not work, but helps the solvent mix with the organic particles, breaks the bonds of the molecules, and reduces the time of disaggregation.…”
Section: Interaction Temperature-chalksupporting
confidence: 86%
“…The temperature rises induce the entropy of the molecules reducing their binding ability, which helps the dissolution of the oily and proteinaceous binders from the inorganic components. The temperature with which we are working had no visible impact on the coccoliths partially corroborating the work of Chairopoulou (92) even though the study of Coto (93) showed an increasing solubility under certain conditions already from 20°C on the contrary. This procedure alone does not work but helps the solvent to mix with the organic particles, breaks the molecules bonds and reduces the time of disaggregation.…”
Section: Interaction Temperature-chalksupporting
confidence: 85%
“…A similar content was obtained for the two methods (48.0% by TG versus 50.8% by muffle furnace) with the advantages of the TG method, which requires only a few milligrams of biomass and is more automated than the muffle method. The high ash content of cultured E. huxleyi when compared with non-coccolithophore microalgae [ 53 ] can be due to the presence of calcium carbonate, as its decomposition is expected above 600 °C [ 54 ].…”
Section: Discussionmentioning
confidence: 99%